Pemanfaatan Metode Fishbone Pada Studi Kasus Keterlambatan Pengembalian Rekam Medis di Rumah Sakit Muhammadiyah Taman Puring - Choirunisa Choirunisa; Lily Widjaja (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT The delay in returning inpatient medical records can show the quality of health services that are less than optimal. To achieve service goals optimally, it is necessary to have a good and supportive system in RM services in accordance with the procedures set out in the hospital. Delay in returning inpatient RM patients will affect and result in the processing and presentation of data starting from assembling activities, analysis, coding, indexing to reporting RM (RM). The purpose of this study was to find out the factors that influence the delay in returning the hospitalization RM to the RM unit at the Muhammadiyah Hospital in Taman Puring using the fishbone method. This type of research is descriptive, population of 253 RM in July 2018 obtained a sample of 155 RM. The technique of collecting data by observation and interviews, the instruments are in the form of interview guidelines, checklists, calculators and return expedition books. Analysis of the data with the percentage of the accuracy of the RM return time and with the Fishbone method get the factors that affect the delay in returning the RM. The results of the study and the discussion that the RM return from the appropriate treatment room was 65.16% and the late ones were 34.83%. The main factor in delaying the return of a patient's RM is a resume that has not been filled in, there is no special officer who returns the hospitalized RM to the RM unit. Keyword: Delay, Return Medical Record, Fishbone.